2002
DOI: 10.1097/00129492-200211000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Saccular Origin of Acoustically Evoked Short Latency Negative Response

Abstract: It is clear that the presence of ASNR is dependent not on residual hearing but on normal saccular function. On the basis of these results, the authors believe ASNR to be saccular in origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 23 publications
5
23
1
1
Order By: Relevance
“…The high-intensity bone-conduction and air-conduction stimuli used in this study were less intense than those they used to elicit optimal VEMPs but may still have been sufficiently loud to elicit a response that could be mistaken for an ASSR. § It is also possible the response originates directly from the vestibular system (Nong et al, 2000). It was not possible to verify a vestibular contribution to the spurious ASSRs recorded in the present study; however, further support for this possibility is provided by subject 10, who reported vestibular effects when presented with high-intensity air-conduction directly to her left ear.…”
contrasting
confidence: 55%
“…The high-intensity bone-conduction and air-conduction stimuli used in this study were less intense than those they used to elicit optimal VEMPs but may still have been sufficiently loud to elicit a response that could be mistaken for an ASSR. § It is also possible the response originates directly from the vestibular system (Nong et al, 2000). It was not possible to verify a vestibular contribution to the spurious ASSRs recorded in the present study; however, further support for this possibility is provided by subject 10, who reported vestibular effects when presented with high-intensity air-conduction directly to her left ear.…”
contrasting
confidence: 55%
“…Loud acoustic stimuli can excite the saccular vestibular epithelium (Nong et al, 2002;Todd et al, 2003;Miyamoto et al, 2007) and evoke a biphasic response in the ipsilateral pre-activated sternocleidomastoid (SCM) muscle (acoustic vestibular evoked cervical myogenic potentials VEMP or cVEMP) through descending vestibulo-spinal pathways. Loud click stimuli, short tone bursts and bone vibration of the mastoid at 500 Hz have been used throughout the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Los estudios clínicos y neurofisiológicos de los que se dispone indican que los VEMP se originan en las aferencias vestibulares del sáculo. Estas señales se transmiten a los núcleos vestibulares y, a través del haz vestibuloespinal, a los músculos ECM 13 . Los VEMP evocados por clics auditivos aparecen en pacientes con hipoacusia neurosensorial, pero no están presentes en sujetos con hipoacusia conductiva 14 .…”
Section: Artículos Originalesunclassified